2015
DOI: 10.1007/s11325-015-1216-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin-10 gene promoter polymorphisms with obstructive sleep apnea

Abstract: The prevalences of the IL-10 gene promoter polymorphisms were different in OSAS patients and the controls in Turkish population. IL-10 gene polymorphisms may lead to altered inflammatory cascade, which might contribute to OSAS. Further studies on larger cohorts are needed to validate our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(46 reference statements)
1
4
0
Order By: Relevance
“…In this study, DNA sequence analysis of the IL-10 gene's promoter in patients with SP revealed 32% of position -1082 guanine into adenine (c. Despite the fact that the global prevalence notified of the allele frequencies of -1082, -819, and -592 SNPs in IL-10 gene in control groups vary, and they are same to last studies in Turkish society [13,21,22].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In this study, DNA sequence analysis of the IL-10 gene's promoter in patients with SP revealed 32% of position -1082 guanine into adenine (c. Despite the fact that the global prevalence notified of the allele frequencies of -1082, -819, and -592 SNPs in IL-10 gene in control groups vary, and they are same to last studies in Turkish society [13,21,22].…”
Section: Discussionsupporting
confidence: 54%
“…IL-10 gene -1082, -819, and -592 positions of the proximal promoter are the most studied polymorphisms. The presence of common allelic combinations in these three SNPs, their linkage disequilibrium and varying IL-10 serum levels that depend on their combinations has been confirmed in several studies [12,13].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…OSAS is a complex and multifactorial syndrome, and it is believed that some specific genes may play a crucial role in its pathogenesis, particularly involved in the expression of the CLOCK gene [7], IL-10 polymorphisms [8], and insulin variable number of tandem repeat (INS VNTR) sequence regulation [9].…”
Section: Risk Factorsmentioning
confidence: 99%